2018
DOI: 10.1542/peds.2017-2039
|View full text |Cite
|
Sign up to set email alerts
|

B6 and Bleeding: A Case Report of a Novel Vitamin Toxicity

Abstract: Pyridox(am)ine-5-phosphate oxidase deficiency is an inborn error of vitamin B6 metabolism that is characterized by neonatal seizures, requiring lifelong therapy with pyridoxal-5-phosphate. We present the first case of a patient with pyridox(am)ine-5-phosphate oxidase deficiency and mild hemophilia A, whose bleeding symptoms were exacerbated by the vitamin B6 therapy essential for his epileptic disorder. This report expands the spectrum of known vitamin B6 toxicity and demonstrates a need for vigilance in monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…53 PLP has an excellent safety profile, although prolonged supraphysiological supplementation may lead to progressive peripheral neuropathy 57,58 , and a dose of 43 mg/kg per day (> 1 gram per day) in a 4 year old patient with hemophilia was associated with recurrent spontaneous hemarthroses. 59 It should also be noted that very high doses of pyridoxine inhibit the active PLP form in vitro. 60 Therefore, it may be prudent to attempt treatment and trials, at least initially, with the PLP form of the vitamin.…”
Section: Plp As a Weapon Against Covid-19mentioning
confidence: 99%
“…53 PLP has an excellent safety profile, although prolonged supraphysiological supplementation may lead to progressive peripheral neuropathy 57,58 , and a dose of 43 mg/kg per day (> 1 gram per day) in a 4 year old patient with hemophilia was associated with recurrent spontaneous hemarthroses. 59 It should also be noted that very high doses of pyridoxine inhibit the active PLP form in vitro. 60 Therefore, it may be prudent to attempt treatment and trials, at least initially, with the PLP form of the vitamin.…”
Section: Plp As a Weapon Against Covid-19mentioning
confidence: 99%
“…Two other reports also are warning case reports. One relates a vitamin B6 toxicity, 19 and the other relates a drug reaction with eosinophilia and systemic symptoms to oxcarbazepine in a patient with a specific immunotype. 20…”
Section: Early Alert Regarding Untoward Consequencesmentioning
confidence: 99%
“…Studies have shown that consuming more vitamin C can increase blood antioxidant levels by up to 30%. 6 Unlike vitamin K2, vitamin K1also called phylloquinone, is obtained from the diet, Deficiency symptoms include possible hemolytic anemia and hyperbilirubinemia (jaundice) in infants. 7 The minerals that are important for complementary infant foods are: magnesium calcium, iron, zinc and manganese.…”
Section: Introductionmentioning
confidence: 99%